Development of a Wearable Exoskeleton with Virtual Reality based Serious Games for Arm Rehabilitation - Jaifani, Alphonsus Sam Rantucci (2018)
This project is aimed to develop a design concept of an upper limb exoskeleton that integrates the use of virtual reality serious games. Due to the increase in population affected by limb disabilities, there is a need for the development of exoskeletons to assist rehabilitations of affected patients. These exoskeletons are attachable to the human body and helps the patients to regain motor controls affected limbs through rehabilitation activities.